Tribal Perspectives on Hypertension: Results From the Center for Native American Health Native-CHART Needs Assessment - Tassy Parker; Allyson Kelley; Norman Cooeyate; Nathania Tsosie (SAGE Publishing, 2022)
Purpose and Objectives: American Indian/Alaska Native (AI/AN) hypertension contributes to cardiovascular disease, the leading cause of premature death in this population. The purpose of this article is to document strategies, concerns, and barriers related to hypertension and cardiovascular disease from Native-Controlling Hypertension and Risks through Technology (Native-CHART) symposiums facilitated by the Center for Native American Health (CNAH). The objectives of this evaluation were to combine Health Needs Assessment (HNA) data and explore barriers and strategies related to hypertension while assessing changes in participants' perspectives over time (2017-2021). Approach: CNAH followed an iterative process each year for planning the HNA, facilitating the HNA, and refining and reflecting on HNA findings over time. This involved 3 interconnected steps: (1) developing a shared understanding for the HNA, "Why are we here?," (2) facilitating the HNA during annual symposiums "What do we do?," and (3) reflecting on "What did we learn?". Evaluation Methods: Data were collected using a culturally centered HNA co-created by the CNAH team and tribal partners. Qualitative data analysis utilized a culturally centered thematic approach and NVivo software version 12.0. Quantitative data analysis included summarizing frequency counts and descriptive statistics using Microsoft Excel. Results: Over the 5-year period, 212 Native-CHART symposium participants completed HNAs. Data collected from HNAs show persistent barriers and concerns and illuminate potential strategies to address AI/AN hypertension. Future efforts must explore effective strategies that build on community strengths, culture and traditions, and existing resources. This is the path forward. Implications for Public Health: CNAH's culturally centered and unique HNA approach helped assess participant perspectives over time. CNAH facilitated symposiums over multiple years, even amid a global pandemic. This demonstrates resilience and continuity of community outreach when it is needed the most. Other universities and tribal partners could benefit from this iterative approach as they work to design HNAs with tribal populations.